Microbiological Assay and Tissue Distribution of β-Thioguanine Deoxyriboside in Mice - Pittillo, Robert F. (1970)
A sensitive, precise microbiological assay has been developed for the determination of tissue distribution of β-thioguanine deoxyriboside, a new antitumor agent.